A Perspective on the Role of microRNA-128 Regulation in Mental and Behavioral Disorders - Ching, Ai-Sze; Ahmad-Annuar, Azlina (Frontiers in Cellular Neuroscience, 2015)
MiRNAs are short, non-coding RNA molecules that regulate gene expression post-transcriptionally. Over the past decade, misregulated miRNA pathways have been associated with various diseases such as cancer, neurodegenerative diseases and neurodevelopmental disorders. In this article, we aim to discuss the role played by miR-128 in neuropsychiatric disorders, and highlight potential target genes from an in silico analysis of predicted miR-128 targets. We also discuss the differences of target gene determination based on a bioinformatics or empirical approach. Using data from TargetScan and published reports, we narrowed the miR-128 target gene list to those that are known to be associated with neuropsychiatric disorders, and found that these genes can be classified into 29 gene clusters and are mostly enriched in cancer and MAPK signaling pathways. We also highlight some recent studies on several of the miR-128 targets which should be investigated further as potential candidate genes for therapeutic interventions.